It is given that an equation of the tangent line to the graph of y=g(x) at x=9 is 6x+9y=27.?
It follows that y=? is the equation of the tangent line to y=g(x^2) at x=3
and that y=? is the equation of the tangent line to y=(g(x))^2 at x=9.

answers:
khalil say: the m of the line
9y = 27 6x
y = (2/3)x  3
m = 2/3
g(x) = ax² + bx + c
g'(x) = 2ax + b
g'(9) = 18a + b = 2/3◄
x = 9 → y = (2/3) (9)  3 = 9
9 = a(9)² + b(9) + c
9 = 81a + 9b +c◄
two equations and three unknowns
assume c = 0
18a + b = 2/3
9 = 81a + 9b
a = 1/27 and b = 4/3
g(x) = (1/27) x²  (4/3) x

Doc say: It's doubtful anybody here can help. Ask your teacher.

otcxy say: yshsdrmc

lhhtf say: tqkkqcrj

rrrrt say: ptzamnnt
